Effect of Slag Content and Carbonation/Ageing on Freeze-Thaw Resistance of Concrete - Iqbal Ahsan; Ojala Teemu; Al-Neshawy Fahim; Punkki Jouni (Nordic Concrete Research)
The construction industry is pursuing the reduction of CO2 emissions and the development of lowcarbon concrete. LOIKKA research project was initiated in Finland with the aim to reduce the CO2 emissions of concrete manufacturing by 50%. The use of blast furnace slag was seen as the most competitive way to significantly reduce CO2 emissions of concrete. However, incorporating slag in concrete can lead to durability complications, particularly concerning salt freeze-thaw resistance. This study investigates the effects of slag content, carbonation/ageing, and pre-curing conditions on the freeze-thaw and salt freeze-thaw resistance of concrete. Additionally, it evaluates the compressive strength development and porosity differences of test concretes. Slab tests were conducted to determine the surface scaling and internal damage resistance of concrete specimens. The results showed that high slag content and carbonation reduced salt freeze-thaw resistance. The incorporation of 50% slag content as the cement clinker replacement is considered critical. An increase in slag content led to a decrease in the compressive strength at 7 days due to the low reactivity of slag but achieved the highest compressive strength at 91 days with 70% slag content. These insights contribute to our understanding of the durability properties of concrete incorporating slag.